Circulating levels of adipocytokine omentin-1 in patients with renal cell cancer. (January 2016) - Shen, Xu-Dong; Zhang, Li; Che, Hong; Zhang, Yang-Yang; Yang, Cheng; Zhou, Jun; Liang, Chao-Zhao
Highlights: Circulating omentin-1 levels were significantly decreased in renal cancer patients. Circulating omentin-1 levels were negatively correlated with WHR and BMI. BMI was the only influential factor significantly related to omentin-1 levels. Circulating omentin-1 levels might have predictive value in RCC diagnosis. Abstract: Renal cell carcinoma (RCC) is the fifth most common cancer worldwide, and becomes one of the leading causes of genitourinary cancer-related death in both males and females. Genetic alternations, alcohol consumption, occupationally harmful exposure and even obesity are well-established risk factors of RCC. Omentin-1 is a plasma adipokine synthesized in visceral adipose tissue, and its circulating serum concentration alters not only in conditions associated with insulin resistance such as Polycystic Ovary Syndrome (PCOS), but also in colorectal cancer and prostate cancer. To our best knowledge, the relationship between omentin-1 and RCC has not been clarified previously. Thus, we evaluated serum omentin-1 levels in RCC patients in the current matched case-control study. Forty-one patients newly diagnosed with RCC and forty-two healthy controls confirmed by the comprehensive medical examination were assessed. The omentin-1 concentrations were determined via utilizing enzyme-linked immunosorbent assays (ELISA) in the paired groups, in which the patients and healthy controls had no statistically significant differences in gender, age, systolic blood pressure (SBP), diastolic blood pressure (DBP), waist-hip ratio (WHR), estimate glomerular filtration rate (eGFR), body-mass index (BMI) and biochemical parameters. The omentin-1 levels in healthy people were 9.86 ± 1.44 ng/mL and the circulating omentin-1 levels were dramatically decreased to 3.62 ± 0.76 ng/mL in RCC patients ( p  < 0.001). Besides, we revealed a negative correlation between omentin-1 with WHR ( r  = −0.261, p  = 0.017) and BMI ( r  = −0.310, p  = 0.004), further indicating BMI was the main influential factor on omentin-1 levels ( p  = 0.0091). Follow-up studies would be conducted to establish the concrete mechanisms underlying the altered circulating levels of omentin-1 and elucidate the interaction between "RCC complex system" and adipose tissues, which may together provide promising and novel pharmacological insights for RCC theragnosis in the near future.